Analysis of the Effect of the Gini Ratio, Percentage of Poor Population, GRDP, HDI, and Average Per Capita Expenditures on Development Inclusivity Index in Java Island - Muftiyatul Azizah (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2022)
This study aimed to analyze whether the Gini ratio, the percentage of poor people, Gross Regional Domestic Product (GDP), Human Development Index (IPM), and average per capita expenditure affect the inclusiveness index of development in Java Island. The method used is panel data regression, namely choosing the best model between the fixed effect model, random effect model, and common effect model and using the classic assumption test. This research is quantitative. The data used in this study are data obtained from BPS and Bappenas from 2014 to 2020. The results show that the factor that has a significant effect on the development inclusiveness index is the Gini ratio with a significance value of 0.0225, the percentage of poor people with a significance value of 0.0015, and Gross Regional Domestic Product (GRDP) with a significance value of 0.0174. Meanwhile, the Human Development Index (IPM) and per capita expenditure have no significant effect on the development inclusiveness index in Java.